2022
DOI: 10.21608/ejhm.2022.267296
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction on the Holistic Care Approach Rendered by Nurses in the Oncology Ward

Abstract: Background: Holistic health care is a crucial part of nursing care, particularly for oncology patients.Objectives: This study aimed to assess the satisfaction of oncology patients with the holistic care approach rendered by the oncology nurses at King Abdullah Medical City in Mecca, Saudi Arabia. Patients and methods: A descriptive quantitative research design was used among 96 oncology patients, who were asked to record their responses through an electronic survey instrument using randomized nonprobability co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…This study was similar to (20) in their study titled "Patient satisfaction on the holistic care approach rendered by nurses in the oncology ward" and stated that more than 75% of the patients were satisfied regarding nursing care provide with mean±SD 191.47 ± 19.51. While, this study was supported by (13) who carried out a study entitled "Elderly cancer patients satisfaction with quality of nursing care in day care unit at oncology center Mansoura University" and demonstrated that more than two thirds of the respondents were dissatisfied with nursing care.…”
Section: Mohamed Ng Nursing Servicessupporting
confidence: 82%
See 1 more Smart Citation
“…This study was similar to (20) in their study titled "Patient satisfaction on the holistic care approach rendered by nurses in the oncology ward" and stated that more than 75% of the patients were satisfied regarding nursing care provide with mean±SD 191.47 ± 19.51. While, this study was supported by (13) who carried out a study entitled "Elderly cancer patients satisfaction with quality of nursing care in day care unit at oncology center Mansoura University" and demonstrated that more than two thirds of the respondents were dissatisfied with nursing care.…”
Section: Mohamed Ng Nursing Servicessupporting
confidence: 82%
“…This result agreed with (19) in their research entitled "Assessing patient satisfaction: using the radiation oncology patient satisfaction questionnaire in a private practice setting" and mentioned a considerable difference between patients' satisfaction and residence. While, such findings were disagreed with (20) in their study titled "Patient satisfaction on the holistic care approach rendered by nurses in the oncology ward" and mentioned that there was no considerable difference between patients' satisfaction and the social status. Also, this study was in disagreement with (24) who performed a research entitled "Predictors of adult patient satisfaction with nursing care in public hospitals of Amhara region, northwest Ethiopia" and stated a noteworthy correlation between patients' satisfaction and their education and age.…”
Section: Mohamed Ng Nursing Servicesmentioning
confidence: 78%